[PS 03-11] PREEXERCISE EVALUATION OF THE HYPERTENSIVE PATIENTS WITH CHRONIC STROKE. (September 2016) - Guseva, Olga; Vichodcev, Andrey; Zhukova, Natalija; Mironova, Julija
Abstract : Objective: Physical activity is recommended for healthy people and patients population, including stroke. However exercises are not without risks. The potential health hazards of the exercises include injury and rare sudden cardiac death. The aim of the present study was to investigate the preexercise condition and risks of the patients with chronic stroke. Design and method: 30 hypertensive patients (15 - male, 15 - female) with hemi paresis and post stroke time from 1 to 15 years were investigated. They were asked about the history of the disease: blood pressure (BP) systolic (SBP) and diastolic before stroke, in acute stroke and post stroke time. The weight and height of the body, the BP, the lung function - forced vital capacity with spirometry, maximal grip strength of the non-affected arm with dynamometry, effect of the posture on BP and pulse, the time of the inspire delay were measured. Analysis was made using Kruskal-Wallis ANOVA and Median Test. Results: All patients had the increase of BP: before stroke, in acute stroke and post stroke time. After stroke SBP decreased in comparison with SBP in acute stroke and before stroke (p < 0.01), but remained increased. Only 5 patients (16.67%) had the normal weight of the body. The rest 83.33% had the obesity. The indices of spirometry and dynamometry were lower in the group of the patients with stroke in comparison with population of the healthy people. In 15 patients the orthostatic function was broken. 7 patients (all - the female) had inspired delay less than 30 s. Conclusions: The chronic stroke patients had the additional factors of the risk: the increasing of the BP, the decreasing of the indices of spirometry and dynamometry, orthostatic intolerance and the impaired adaptation to the decreasing of the oxygen and must be evaluated before exercises to minimize the adverse effects during rehabilitation.